2015
DOI: 10.1080/17461391.2015.1031712
|View full text |Cite
|
Sign up to set email alerts
|

Upper limb joint muscle/tendon injury and anthropometric adaptations in French competitive tennis players

Abstract: The purpose of this study was to examine the relationship between the upper limb anthropometric dimensions and a history of dominant upper limb injury in tennis players. Dominant and non-dominant wrist, forearm, elbow and arm circumferences, along with a history of dominant upper limb injuries, were assessed in 147 male and female players, assigned to four groups based on location of injury: wrist (n = 9), elbow (n = 25), shoulder (n = 14) and healthy players (n = 99). From anthropometric dimensions, bilateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
(40 reference statements)
1
11
0
Order By: Relevance
“…The lack of difference in their strength ratios may reinforce the importance of developing the dominant side in symmetric proportion to the nondominant side to preserve physical integrity. 47 From an early age, a strength balance in the dominant rotator cuff and scapular muscles is crucial to maintaining humeral head congruence in the glenoid cavity when the upper extremity carries out tennis movements.…”
Section: Maximal Isometric Strength Of the Shoulder-complex Musclesmentioning
confidence: 99%
“…The lack of difference in their strength ratios may reinforce the importance of developing the dominant side in symmetric proportion to the nondominant side to preserve physical integrity. 47 From an early age, a strength balance in the dominant rotator cuff and scapular muscles is crucial to maintaining humeral head congruence in the glenoid cavity when the upper extremity carries out tennis movements.…”
Section: Maximal Isometric Strength Of the Shoulder-complex Musclesmentioning
confidence: 99%
“…So we continued to assess R F values only up to a fstep of 75 kHz. Figure 2 shows the regression curve of the R Fr-l values versus the corresponding f step and it is well represented (P = 0.003) by the equation (1).…”
Section: Resultsmentioning
confidence: 77%
“…Changes in the structural composition of the arm of one side with respect to that of the other side often may indicate not only proper adaptations in that arm, like as what happens in athletes engaged in asymmetric sports specialties [1], but also several illness occurring in other body organs. In fact, it has been found that a lot of post -breast cancer people shows accumulation of lymph fluid in the arm of the affected side [2].…”
Section: Introductionmentioning
confidence: 99%
“…A symmetry index (SI) was used to calculate the difference, expressed as a percentage, between the extracted dominant and non-dominant upper extremity BMC values using the following formula: SI = ((dominant BMC/ non-dominant BMC) -1) x 100 (Rogowski et al, 2016). Two researchers (LC and NR) independently assessed risk of bias using the Joanna Briggs Institute (JBI) critical appraisal tool for Analytical Cross-sectional or Cohort Studies (Moola et al, 2017).…”
Section: Data Extraction and Risk Of Bias Assessmentmentioning
confidence: 99%